Malay Culture in Audio Visual Media as a Learning Model for BIPA - Maulida Mandasari Lubis; Dian Syahfitri; Dapot H Bakkara; Hetty Kusniawaty; E Sri Mehulinta Sembiring (Universitas Majalengka, 2025)
This study aims to analyze the use of audio visual media in learning Indonesian for Foreign Speakers (BIPA). One of the main challenges in BIPA learning is the low motivation of participants. This lack of motivation is often caused by the monotonous classroom atmosphere. To increase learning motivation, an interesting and innovative approach is needed, especially for teenage and early adult participants. This research uses a descriptive qualitative method with a case study approach. The research subjects were beginner level participants of the Indonesian for Foreign Speakers Program (BIPA) at Prima University Medan, while the research object was the use of audiovisual media in BIPA learning. The results showed that audiovisual media can be used effectively to support BIPA learning objectives. Audio Visual are able to facilitate the learning of listening, speaking, reading, and grammar, while creating a more pleasant classroom atmosphere. In addition to entertaining and attracting participants’ interest, audovisual also have various other benefits in BIPA learning. It is recommended for practitioners to continue to develop and integrate audiovisual media into BIPA learning materials.